Pengaruh Kesadaran Perpajakan, Penyuluhan Perpajakan, Lingkungan, Sanksi Denda Dan Sikap Fiskus Terhadap Kepatuhan Wajib Pajak (Studi Empiris di Kantor Pelayanan Pajak Pratama Sukoharjo) - Zulaika, Windy; , Dra. Mujiyati, M.Si (2016)
The purpose of this study was to analyze and test the effect of tax penalties, the attitude of the tax authorities, tax counseling, tax awareness and environmental impact on tax compliance in KPP PratamaSukoharjo.Penelitian district uses a quantitative method using primary data obtained from questionnaires. The population in this study are all taxpayers in KPP PratamaSukoharjo district. The number of samples in this study as many as 100 individual taxpayers in KPP PratamaSukoharjo district. Methods of sample collection using techniques slovin formula with purposive sampling method. The analytical tool used include validity and reliability test, normality test, multicollinearity, heteroscedasticity test, multiple linear regression, F test, test the coefficient of determination R, and t.Berdasarkan test results of data analysis can be concluded that the variable tax penalties significant negative effect on tax compliance, while attitudinal variables fiskus significant positive effect on tax compliance, then the variable extension taxation significant positive effect on tax compliance, then the variable consciousness taxation significant positive effect on tax compliance, Begitupula environment variables significant positive effect on compliance taxpayers, so it is with the test simultaneously (synchronously) shows the statistical test of distribution F test signifikansehingga regression model was fit. Adjusted R2artinya tax penalties, the attitude of the tax authorities, tax counseling, tax and environmental awareness are able to explain the variability of mandatory compliance